Project delays in the Niger Delta Region, Nigeria : Significant causes, effects and solutions. - Jacob, Unwana Nyong. (My University, 2013)
This study investigates causes and effects of infrastructural project delays in the Niger Delta region, Nigeria using literature and questionnaire surveys. Potential benefits and beneficiaries of project delays were also investigated. Research participants were public service, multinational and private companies’ project practitioners. Participants perceived that, there were eleven most important causes of delays. The first five are: youth unrest, militancy and communal crises; inadequate planning by the contractors; delay or non-payment of compensation to the communities; wrong choice of consultants and contractors by the clients; and weather condition. Time overrun; budget overrun; and disputes and claims were perceived as the most important effects of delays. Participants also perceived that delays mostly occur in roads/bridges, shore protection and channelization projects. The study suggests that, delays could be curtailed through dialogue and careful management of militants/communal crises, proper planning by contractors, prompt release of funds and engagement of qualified vendors by clients.